A systematic review with meta-analysis: Traditional Chinese tuina therapy for insomnia - Wang, Zheng; Xu, Hui; Zhou, Hang; Lei, Yang; Yang, Lulu; Guo, Juan; Wang, Yuxia; Zhou, Yunfeng (Frontiers in Neuroscience, 2023)
Background With changes in the way of life and work, an increasing number of people are suffering from insomnia. In China, a traditional Chinese medicine method tuina is widely used for the treatment of insomnia. However, the evidence for tuina therapy for insomnia remains controversial. Therefore, this systematic review aimed to evaluate the effect of tuina therapy on the symptoms of patients with primary insomnia. Methods From establishment to January 2022, a comprehensive literature search was conducted using seven electronic databases to identify randomized controlled trials of tuina therapy for insomnia. We used RevMan 5.4 software and the GRADEpro Guideline Development Tool to evaluate the quality of the included randomized controlled trials and perform the meta-analysis. The methodological quality of the included studies was assessed using the Cochrane risk-of-bias tool. Subgroup analysis was performed according to the different intervention methods. The I2 statistic was used to assess the heterogeneity. Results Eighteen studies conducted from 2011 to 2021 were included, with a total of 1,471 patients. In terms of efficacy, tuina alone was superior to other treatments [odds ratio (OR), 3.46; 95% confidence interval (CI), 2.15, 5.55; P < 0.00001]; tuina combined with other treatments (acupuncture, scraping, auricular acupuncture, Suanzaoren decoction, estazolam) was more effective than other single therapies (OR, 3.99; 95% CI, 2.84, 5.61; P < 0.00001). In terms of Pittsburgh Sleep Quality Scale score, the improvement in insomnia patients by tuina alone was better than that of other treatments [standardized mean difference (SMD), −2.57; 95% CI, −2.98, −2.17; P < 0.00001], and tuina combined with other treatments (acupuncture, scraping, auricular point pressing, Suanzaoren decoction, estazolam) was better than other single therapies (SMD, −2.83; 95% CI, −2.98, −2.68; P < 0.00001). Conclusion This meta-analysis revealed that tuina can significantly improve the clinical efficacy and sleep quality of patients with primary insomnia. This study provides a theoretical basis and treatment guidance for patients with primary insomnia. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42022355742.